Development and Validation of a Servant Leadership Scale in Indonesian Christian Higher Education: Pretest and Post-Test - Dami, Zummy Anselmus (Christian higher education, 2025)
The Servant Leadership Scale has been developed in the context of the university. This scale has seven dimensions: behaving ethically, development, emotional healing, empowerment, pioneering, relationship building, and wisdom. Furthermore, this scale was modified into six dimensions: authenticity, behaving ethically, development, emotional healing, humility, and wisdom. To date, this scale has only been tested in universities and the public sector, while it has never been studied in Indonesian Christian higher education. This study aimed to validate the scale of servant leadership of Christian education leaders in Indonesia. The method is quantitative, with second-order confirmatory factor analysis. This study used a survey of 180 lecturers in Christian higher education in East Java, Indonesia. The analysis was carried out with the help of SmartPLS 4. The analysis employing pretest, first and second-order (post-test) indicates that all indicators of servant leadership are valid, reliable, and constitute a multidimensional construct with nine dimensions. These dimensions include behaving ethically, development, emotional healing, empowerment, pioneering, relationship building, wisdom, transcendental spirituality, and motivation to serve. This study concludes that the Servant Leadership Scale suits Indonesian culture and can be used for research in religious universities.